PHYSIOLOGICAL RESPONSES AT VARIOUS LACTATE MARKERS FOR RUNNING AT 4 AND 8 MINUTE TREADMILL INCREMENTS - James Peter Gavin; Stephen Daniel Myers; Marc Elizabeth Theodorus Willems (Sport Scientific And Practical Aspects, 2025)
We compared physiological responses corresponding to speeds at plasma lactate markers between incremental treadmill running of 4 and 8 min stages in fifteen healthy men (23 ± 4 yrs, 1.78 ± 0.49 m, 72.7 ± 10.8 kg).Treadmill speed, oxygen uptake (VO2), heart rate (HR), rating of perceived exertion (RPE) and plasma lactate were measured for each stage, and calculated at: fixed blood lactate accumulation (FBLA) 4.0 mmol/L, an initial 1 mmol/L rise, deviation maximum (Dmax), lactate threshold (LT) and log-log LT. There was no effect (p>0.05) of stage duration on speed, VO2, HR and RPE at fixed markers. For 8 min stages, speed was lower at modelled markers: Dmax(-1.1 km/h; p=0.001), LT (-0.9 km/h; p=0.008) and log-log LT (-0.8 km/h; p=0.006), yet RPE was higher and VO2lower for LT (1.1, p= 0.02; -0.27 L/min, p=0.01) and log-log LT (1.4, p=0.03; -0.29 L/min, p=0.002). Lactate and VO2 were greater at 8km/h for 4 min (p=0.0001), then similar until 11 km/h, with a trend towards elevated plasma lactate for 4 min thereafter. When applying lactate threshold markers to assess physiological responses to incremental running, protocols using prolonged stage durations may underestimate marker running speed.